RNA-Binding Proteins at the Host-Pathogen Interface Targeting Viral Regulatory Elements - Embarc-Buh, Azman (Viruses, 2021)
Viral RNAs contain the information needed to synthesize their own proteins, to replicate, and to spread to susceptible cells. However, due to their reduced coding capacity RNA viruses rely on host cells to complete their multiplication cycle. This is largely achieved by the concerted action of regulatory structural elements on viral RNAs and a subset of host proteins, whose dedicated function across all stages of the infection steps is critical to complete the viral cycle. Importantly, not only the RNA sequence but also the RNA architecture imposed by the presence of specific structural domains mediates the interaction with host RNA-binding proteins (RBPs), ultimately affecting virus multiplication and spreading. In marked difference with other biological systems, the genome of positive strand RNA viruses is also the mRNA. Here we focus on distinct types of positive strand RNA viruses that differ in the regulatory elements used to promote translation of the viral RNA, as well as in the mechanisms used to evade the series of events connected to antiviral response, including translation shutoff induced in infected cells, assembly of stress granules, and trafficking stress.